Comparative Analysis of in vitro Digestibility and Immunogenicity of Gliadin Proteins From Durum and Einkorn Wheat - Di Stasio, Luigia; Picascia, Stefania; Auricchio, Renata; Vitale, Serena; Gazza, Laura; Picariello, Gianluca; Gianfrani, Carmen; Mamone, Gianfranco (Frontiers in Nutrition, 2020)
Recent studies suggested that gliadin proteins from the ancient diploid einkorn wheat Triticum monococcum retained a reduced number of immunogenic peptides for celiac disease patients because of a high in vitro digestibility respect to hexaploid common wheat. In this study, we compared the immunological properties of gliadins from two Triticum monococcum cultivars (Hammurabi and Norberto-ID331) with those of a Triticum durum cultivar (Adamello). Gliadins were digested by mimicking the in vitro gastrointestinal digestion process that includes the brush border membrane endopeptidases. Competitive ELISA, based on R5 monoclonal antibody, showed that gastrointestinal digestion reduced the immunogenicity of Triticum monococcum gliadins; conversely the immunogenic potential of Triticum durum gliadins remained almost unchanged by the in vitro digestion. The immune stimulatory activity was also evaluated by detecting the IFN-γ production in gliadin-reactive T-cell lines obtained from the small intestinal mucosa of HLA-DQ2+ celiac disease patients. Interestingly, gastrointestinal digestion markedly reduced the capability of Triticum monococcum gliadins (p<0.05) of both cultivars to activate T cells, whilst slightly affected the activity of Triticum durum. In conclusion, our results showed that Triticum durum was almost unaffected by the in vitro gastrointestinal digestion, whilst Triticum monococcum had a marked sensibility to digestion, thus determining a lower toxicity for celiac disease patients.